Computational Modeling of Glucose Uptake in the Enterocyte - Afshar, Nima; Safaei, Soroush; Nickerson, David P.; Hunter, Peter J.; Suresh, Vinod (Frontiers in Physiology, 2019)
Absorption of glucose across the epithelial cells of the small intestine is a key process in human nutrition and initiates signalling cascades that regulate metabolic homeostasis. Validated and predictive mathematical models of glucose transport in intestinal epithelial cells are essential for interpreting experimental data, generating hypotheses and understanding the contributions of and interactions between transport pathways. Here we report on the development of such a model that, in contrast to existing models, incorporates mechanistic descriptions of all relevant transport proteins and is implemented in the CellML framework. The model is validated against experimental and simulation data from the literature. It is then used to elucidate the relative contributions of the sodium-glucose cotransporter (SGLT1) and the glucose transporter type 2 (GLUT2) proteins in published measurements of glucose absorption from human intestinal epithelial cell lines. The model predicts that the contribution of SGLT1 dominates at low extracellular glucose concentrations (<20 mM) and short exposure times (<60 s) while the GLUT2 contribution is more significant at high glucose concentrations and long durations. Implementation in CellML permitted a modular structure in which the model was composed by reusing existing models of the individual transporters. \textcolor{red}{The final structure also permits transparent changes of the model components and parameter values in order to facilitate model reuse, extension and customisation (for example, to simplify or add complexity to specific transporter/pathway models, or reuse the model as a component of a larger framework) and carry out parameter sensitivity studies.